Equivalence between classical and quantum dynamics : Neutral kaons and electric circuits - Caruso, Mariano Guillermo (2011)
An equivalence between the Schrodinger dynamics of a quantum system with a finite number of basis states and a classical dynamics is presented. The equivalence is an isomorphism that connects in univocal way both dynamical systems. We treat the particular case of neutral kaons and found a class of electric networks uniquely related to the kaon system finding the complete map between the matrix elements of the effective Hamiltonian of kaons and those elements of the classical dynamics of the networks. As a consequence, the relevant ϵ parameter that measures CP violation in the kaon system is completely determined in terms of network parameters.